Aniba subbullata (Lauraceae), a new species from the Chapada Diamantina, Bahia, Brazil with notes on the leaf epidermis of congeneric species - Ribeiro, Henrique Lauand [UNESP]; Coan, Alessandra Ike [UNESP]; de Moraes, Pedro Luís Rodrigues [UNESP] (Wiley, 2018)
A new plant species from Chapada Diamantina, Bahia, Brazil, Aniba subbullata, is described and illustrated. Its putative relationships within the genus are discussed, and an identification key is provided for distinguishing it from previously known species in that state. We also provide illustrations and comments on micromorphological features of leaves of this new species, particularly of the abaxial surface, comparing them to those of congeneric species and showing that they are useful for its recognition.
Keywords: Laurales; leaf cuticles; leaf papillosity; Neotropics; taxonomy